Sintering of porous alumina obtained by biotemplate fibers for low thermal conductivity applications - Delbrücke, Tiago; Gouvêa, Rogério A.; Moreira, Mário L.; Raubach, Cristiane W.; Varela, José Arana [UNESP]; Longo, Elson [UNESP]; Gonçalves, Margarete R.F.; Cava, Sergio (Elsevier, 2013)
In this research report, a sintering process of porous ceramic materials based on Al2O3 was employed using a method where a cation precursor solution is embedded in an organic fibrous cotton matrix. For porous green bodies, the precursor solution and cotton were annealed at temperatures in the range of 100-1600°C using scanning electron microscopy (SEM) and thermogravimetric (TG) analysis to obtain a porous body formation and disposal process containing organic fibers and precursor solution. In a structure consisting of open pores and interconnected nanometric grains, despite the low porosity of around 40% (calculated geometrically), nitrogen physisorption determined a specific surface area of 14m2/g, which shows much sintering of porous bodies. Energy dispersive X-ray (EDX) and X-ray diffraction (XRD) analytical methods revealed a predominant amount of α-Al2O3 in the sintered samples. Thermal properties of the sintered Al2O3 fibers were obtained by using the Laser Flash which resulted in the lower thermal conductivity obtained by α-Al2O3 and therefore improved its potential use as an insulating material. © 2012 Elsevier Ltd.
Keywords: Al2O3; Chemically synthesized; Replica method in organic matrix; Sintered porous body; Thermal properties; Analytical method; Disposal process; Energy dispersive x-ray; Green body; Laser flash; Low porosity; Low thermal conductivity; Nanometrics; Organic fibers; Organic matrix; Porous alumina; Porous bodies; Porous ceramic materials; Precursor solutions; Research reports; Sintered samples; Sintering process; Thermogravimetric; Aluminum; Cotton; Physisorption; Scanning electron microscopy; Thermal conductivity; Thermodynamic properties; Thermogravimetric analysis; X ray diffraction; Sintering; Gravimetry; Scanning Electron Microscopy; Thermal Analysis; Thermal Conductivity; Thermal Properties; X Ray Diffraction